2010
DOI: 10.1016/j.ajog.2010.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Fecal incontinence in older women: are levator ani defects a factor?

Abstract: Objective To compare pelvic floor structure and function between older women with and without fecal incontinence (FI) and young continent women. Study Design Young (YC, n=9) and older (OC, n=9) continent women were compared to older women with FI (OI, n=8). Patients underwent a POP-Q, measurement of levator ani (LA) force at rest (FLAR) and with maximum contraction (FLAC), and MRI. Displacement of structures and LA defects were determined on dynamic MRI. Results LA defects were more common in the OI v. the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 22 publications
(28 reference statements)
1
32
0
3
Order By: Relevance
“…As shown previously we expected women with major avulsions to report more faecal incontinence, as the incidence of OASIS was higher (n = 8/30) (K. W. M. Van Delft, R. Thakar, A. H. Sultan, N. Schwertner-Tiepelmann, K. B. Kluivers [accepted]. Although two studies among older women showed an association between faecal incontinence and LAM avulsion, 17,19 another study in a tertiary referral centre showed the opposite. 20 The incidence of urinary incontinence prior to childbirth can be explained by the physiological changes that occur during pregnancy and the load of the gravid uterus predisposing women to urinary incontinence.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As shown previously we expected women with major avulsions to report more faecal incontinence, as the incidence of OASIS was higher (n = 8/30) (K. W. M. Van Delft, R. Thakar, A. H. Sultan, N. Schwertner-Tiepelmann, K. B. Kluivers [accepted]. Although two studies among older women showed an association between faecal incontinence and LAM avulsion, 17,19 another study in a tertiary referral centre showed the opposite. 20 The incidence of urinary incontinence prior to childbirth can be explained by the physiological changes that occur during pregnancy and the load of the gravid uterus predisposing women to urinary incontinence.…”
Section: Discussionmentioning
confidence: 92%
“…Although the relationship between LAM avulsion and faecal [17][18][19][20] and urinary incontinence [21][22][23][24][25] has been evaluated, sexual function has not been studied in relation to LAM avulsion. We are not aware of a study in the literature that has utilised validated methods for objective and subjective assessment of PFD in relation to LAM avulsion before and after childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…On MRI, images are assessed for significant asymmetry, in the morphology of the right and left sides of the muscle in an individual patient, and excessive ballooning [78]. Larger genital hiatus and a greater fixed and dynamic perineal descent are seen in patients with abnormal levator muscle [79,80]. In addition, major muscle loss can be seen in combination with external anal sphincter injury on MRI in postpartum patients [61].…”
Section: Pelvic Floor Integritymentioning
confidence: 99%
“…44,45 Although there is variability in the appearance of the pelvic support structures even in asymptomatic nulliparous women, 46 significant differences in levator muscle volume, shape, and integrity have been shown between asymptomatic individuals and those with incontinence and pelvic prolapse. 47 The levator muscles should be assessed for areas of asymmetric thickening or atrophy (Fig.…”
Section: Anatomic Evaluationmentioning
confidence: 99%